The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/adhm.201600532
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Implant Acceptance and Wound Healing: Material Selection and Implant Location Modulate Macrophage and Fibroblast Phenotypes

Abstract: This review focuses on materials and methods used to induce phenotypic changes in macrophages and fibroblasts. Herein, we give a brief overview on how changes in macrophages and fibroblasts phenotypes are critical biomarkers for identification of implant acceptance, wound healing effectiveness, and are also essential for evaluating the regenerative capabilities of some hybrid strategies that involve the combination of natural and synthetic materials. The different types of cells present during the host respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 204 publications
(254 reference statements)
0
75
0
Order By: Relevance
“…This dynamic in the capsule formation is coincident in time with the infiltration of macrophages in the nerve due to the implant described here which also peaked after 2 weeks and started to decrease thereafter (49) . It has been shown that macrophages and phagocytes are related with the nature of the material implanted and its degradation dynamics (50), (51) . Thus, biodegradable materials would stimulate a more M1 and phagocytic environment to eliminate the implant.…”
Section: Discussionmentioning
confidence: 99%
“…This dynamic in the capsule formation is coincident in time with the infiltration of macrophages in the nerve due to the implant described here which also peaked after 2 weeks and started to decrease thereafter (49) . It has been shown that macrophages and phagocytes are related with the nature of the material implanted and its degradation dynamics (50), (51) . Thus, biodegradable materials would stimulate a more M1 and phagocytic environment to eliminate the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on investigating the interaction between implanted biomaterials and the host response that causes capsular contracture via FBRs to improve the function and durability of PDMS‐based silicone implants . Although the mechanism of FBRs against PDMS implants has not yet been fully understood, it has been accepted that several cells including macrophages, fibroblasts, and myofibroblasts play a key role in encapsulating the implant with a dense collagenous avascular capsule . In particular, nonspecific protein adsorption and macrophage adhesion in the initial inflammatory process promote the overall FBRs.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Although the mechanism of FBRs against PDMS implants has not yet been fully understood, it has been accepted that several cells including macrophages, fibroblasts, and myofibroblasts play a key role in encapsulating the implant with a dense collagenous avascular capsule. [9][10][11][12] In particular, nonspecific protein adsorption and macrophage adhesion in the initial inflammatory process promote the overall FBRs. Therefore, it has been considered important to suppress the FBRs by reducing the cell adhesion at the surface of the implant and controlling the cell behavior by modifying the characteristics of the implant such as surface chemistry and topography.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of macrophages was initially documented in 1975 through a series of anti-serum and steroid suppression experiments where, unlike neutrophils, impaired or depleted macrophages had a negative impact on the time to wound healing. After these initial experiments, subsequent data confirmed these findings and it is now widely recognized that macrophages function as a critical regulatory cell in wound healing [37,45,46]. …”
Section: Wound-healing Overviewmentioning
confidence: 69%